Dampak Agrowisata Terhadap Perubahan Sosial Budaya Masyarakat Di Desa Wisata Sembalun Bumbung, Lombok Timur - Ruhiyawati, Ruhiyawati; Nugroho, Saptono; Narottama, Nararya (JURNAL DESTINASI PARIWISATA, 2023)
This research was conducted based on the conditions of agrotourism development in the Sembalun Bumbung Tourism Village, East Lombok Regency, which is quite developed, seen from the emergence of agrotourism businesses. This research aims to determine the impact of agrotourism activities on socio-cultural changes in society. This research uses a qualitative approach, with primary data sources and secondary data. The data collection technique was carried out by direct observation eight times, in-depth interviews with six informants determined using purposive sampling techniques including the Sembalun Bumbung Village Head, Pokdarwis Chair, Traditional Chair, Farmers, Traders, and Agrotourism Entrepreneurs and documentation to complete the data. has been obtained through observation methods. The data analysis technique uses qualitative descriptive analysis techniques. This research shows that agrotourism activities have an impact on the community in the Sembalun Bumbung Tourism Village which is seen from four aspects, including: the impact on livelihoods, namely the transformation of the livelihood structure from the agricultural sector to the tourism sector and increasing community income, the impact on social deviation, namely cases Social deviation is relatively low due to public awareness of the importance of maintaining security, the impact on social organizations/institutions, namely the formation of community organizations which have become a forum for developing the Sembalun Bumbung Tourism Village and the impact on arts and customs, namely the values contained in each existing tradition are still implemented. and maintained and preserved. Suggestions that can be given to the government and tourism service entrepreneurs in Sembalun Bumbung Village are to embrace local communities so they are able to collaborate with tourism entrepreneurs and pay more attention to local communities in taking advantage of business and employment opportunities. Keywords: Impact, Agrotourism, Socio-Cultural Change